God's universe - Gingerich, Owen. (Cambridge, Mass. : Belknap Press of Harvard University Press, 2006)
"Owen Gingerich believes in a universe of intention and purpose. Taking Johannes Kepler as his guide, Gingerich argues that an individual can be both a creative scientist and a believer in divine design - that indeed the very motivation for scientific research can derive from a desire to trace God's handiwork. Gingerich carves out "a theistic space" from which it is possible to contemplate a universe where God plays an interactive role, unnoticed yet not excluded by science."--BOOK JACKET.
1. Is mediocrity a good idea? -- 2. Dare a scientist believe in design? -- 3. Questions without answers.
Includes bibliographical references (p. [123]-131) and index.
Keywords: Religion and science